PENGARUH PENGGUNAAN MEDIAL ARCH SUPPORT TERHADAP VERTICAL JUMP PADA PEMAIN BASKET - Utomo, Prasetyo Catur; Anggriani, Atika Febri; Ferio, Akbar (Medical Journal of Nusantara, 2024)
Background: Someone who does regular sports activities, exercising regularly, improves the quality of a person's health. One sport that can be an option to achieve this goal is basketball. The basic techniques in basketball are:shooting (shooting), passing (baiting), dribbling (herding), pivoting (resting on one leg), and rebounding. In this sport, vertical jump is one of the elements that determines success in carrying out several of these techniques. The aim of this research is to analyze the influence of media usearch support on the basketball player's jump and look for medial support that has an effect on the vertical jump. Method and subject: This type of research is pre-experimental research. The subjects in this research were 30 male members of the Surakarta Health Polytechnic basketball UKM, which was carried out in March–April 2023. Results: Data normality was carried out using the Shapiro-Wilk test (<50), and the data was normally distributed with a significant value of p = 0.707 and p = 0.957 in the pre-test and post-test. The hypothesis test used is the paired sample T test with a sig value of 0.010 (P <.0.05) and a very high correlation strength of 0.827. Conclusion: There is an influence of medial usearch support for vertical jump on basketball players at UKM Poltekkes Surakarta